Klotho has dual protective effects on cisplatin-induced acute kidney injury - Panesso, Monica Chang (2013)
Klotho protects the kidney from ischemia-reperfusion injury, but its effect on nephrotoxins is unknown. Here we determined if Klotho protects the kidney from cisplatin toxicity. Cisplatin increased plasma creatinine and induced tubular injury, which were exaggerated in Klotho haplosufficient (Kl/+) and ameliorated in transgenic Klotho overexpressing (Tg-Kl) mice. Neutrophil gelatinase-associated lipocalin and active caspase-3 protein, and number of apoptotic cells in the kidney were higher in Kl/+ and lower in Tg-Kl compared to wild type mice. Klotho suppressed basolateral uptake of cisplatin by the normal rat kidney cell line (NRK); an effect similar to cimetidine, a known inhibitor of organic cation transport (OCT). A decrease in cell surface and total OCT2 protein and OCT activity by Klotho was mimicked by glucuronidase. The Klotho effect was attenuated by glucuronidase inhibition. On the other hand, OCT2 mRNA was reduced by Klotho, but not β-glucuronidase. Moreover, cimetidine inhibited OCT activity but not OCT2 expression. Unlike cimetidine, Klotho reduced cisplatin-induced apoptosis from either the basolateral or apical side, and even when added after NRK cells were already loaded with cisplatin. Thus, Klotho protects the kidney against cisplatin nephrotoxicity by reduction of basolateral uptake of cisplatin by OCT2, and a direct anti-apoptotic effect independent of cisplatin uptake. Klotho may be a useful agent to prevent and treat cisplatin-induced nephrotoxicity.